Đáp án:
Giải thích các bước giải:
$\begin{array}{l}
C_{2n}^2 - 2C_n^2 - {n^2} = 0\\
\Rightarrow \frac{{\left( {2n} \right)!}}{{2!.\left( {2n - 2} \right)!}} - 2\frac{{n!}}{{2!.\left( {n - 2} \right)!}} - {n^2} = 0\\
\Rightarrow \frac{{2n\left( {2n - 1} \right)}}{2} - n.\left( {n - 1} \right) - {n^2} = 0\\
\Rightarrow n\left( {2n - 1} \right) - {n^2} + n - {n^2} = 0\\
\Rightarrow 2{n^2} - n - {n^2} + n - {n^2} = 0\\
\Rightarrow 0 = 0\left( {dung\forall n} \right)\\
vay\,C_{2n}^2 - 2C_n^2 - {n^2} = 0\,\forall n>0
\end{array}$